KOLABORASI SENI PADA UPACARA PENGOBATAN SUKU KAILI - Hastuti, Sri; Lembah, Gazali; Ulinsa, Ulinsa (BAHASANTODEA, 2017)
This thesis is focused on art collaboration in medication ceremony of kailinese. The research problem was from an meaning contained in art collaboration in medication ceremony balia tampilangi Ulujadi at donggala kodi of padanjese village. The research aims to describe form and meaning of art collaboration in medication ceremony of kailinese. This research used descriptive qualitative method with hermeneutics approach. Data source of the research was from medication ceremony process of balia tampilangi Ulujadi of kailinese. Technique of data collection was direct observation, interview, documentation, and triangulation. Data analysis covered data collection, data reduction, data display and drawing conclusion. The results indicate that art collaboration in medication ceremony of balia tampilangi Ulujadi includes some forms of art, namely (1) drum and gong, (2) dance art covers movemenst of hand and foot, (3) theatre art covers popasaki, popanjaku of poraro, toratabolu, pokavu. (4) fine art consists of two dimensions and three dimensions. Two dimensions fine art cover bangunjaro and gulinto, siga, kayu mpovera and gantulili, lumbu, langi-langi, while three dimensions cover costume.